Role of ventriculovascular coupling in cardiac response to increased contractility in closed-chest dogs. - Freeman, G L (1990)
While both dobutamine and pacing tachycardia augment left ventricular (LV) contractility, whether overall cardiovascular response to these stimuli is comparable is not known. To address this question we studied seven dogs previously instrumented with three LV diameter gauges and LV pressure manometers. After ganglionic blockade and sedation, caval occlusions were performed at heart rates of 120, 160, and 200 bpm before (C), and 160 and 200 bpm after administration of 10 micrograms/kg per min dobutamine, i.v. (D). The effective arterial elastance (Ea) went up from 14.2 +/- 4.5 mmHg/ml at C120 to 19.6 +/- 8.8 (P less than 0.025 vs C120) and 24.2 +/- 10.4 (P less than 0.001 vs C120) mmHg/ml at C160 and C200. Ees, the slope of the end-systolic pressure-volume relation, increased with pacing from 9.7 +/- 4.6 to 11.7 +/- 4.3 (P less than 0.02), and 13.2 +/- 5.7 (P less than 0.02) mmHg/ml at 160 and 200 bpm. With dobutamine infusion Ea went down, and Ees was further increased to 37.0 +/- 20.9 mmHg/ml at 160 bpm (P less than 0.002 vs C160), and 53.0 +/- 22.6 mmHg/ml at 200 bpm (P less than 0.002 vs C200). Comparison of stroke work and pressure-volume area from single beats with matched LV end-diastolic volumes showed that these were both increased by dobutamine, but not by pacing tachycardia. While increased heart rate after dobutamine markedly increased contractility, Ea was not changed, and neither stroke work nor pressure-volume was further increased. Thus, how well an increase in contractility is transmitted to the periphery is determined in part by arterial behavior. Assessment of both the arterial system and cardiac contractility is necessary to fully evaluate the overall impact of an inotropic stimulus.